The early stage of bacterial genome-reductive evolution in the host. - Han Song (Public Library of Science (PLoS), 2010)
The equine-associated obligate pathogen Burkholderia mallei was developed by reductive evolution involving a substantial portion of the genome from Burkholderia pseudomallei, a free-living opportunistic pathogen. With its short history of divergence (approximately 3.5 myr), B. mallei provides an excellent resource to study the early steps in bacterial genome reductive evolution in the host. By examining 20 genomes of B. mallei and B. pseudomallei, we found that stepwise massive expansion of IS (insertion sequence) elements ISBma1, ISBma2, and IS407A occurred during the evolution of B. mallei. Each element proliferated through the sites where its target selection preference was met. Then, ISBma1 and ISBma2 contributed to the further spread of IS407A by providing secondary insertion sites. This spread increased genomic deletions and rearrangements, which were predominantly mediated by IS407A. There were also nucleotide-level disruptions in a large number of genes. However, no significant signs of erosion were yet noted in these genes. Intriguingly, all these genomic modifications did not seriously alter the gene expression patterns inherited from B. pseudomallei. This efficient and elaborate genomic transition was enabled largely through the formation of the highly flexible IS-blended genome and the guidance by selective forces in the host. The detailed IS intervention, unveiled for the first time in this study, may represent the key component of a general mechanism for early bacterial evolution in the host.